Perubahan Gaya Resitasi Raja Guhya Yoga dalam Bhagawad Gita: Studi Kasus di Pura Mutihan Sangga Buana Klaten - Nugraha, Ichsandy Kurnia (Institut Seni Indonesia (ISI) Surakarta, 2019)
This scientific research, entitled “Changes in the Recitation Style of Raja Guhya Yoga in the Bhagavad Gita: Case Study at the Mutihan Sangga Buana Temple in Klaten”, is based at the aforementioned phenomena observed on the dharma gita at Pura Mutihan Sangga Buana, Gantiwarno, Klaten. Musical changeshave happenedin the way scriptures are recited, particularly in regard with the sloka form. Changes in the developingrecitation systems and methods become important to be studied and written on academic papers. Initially, the dharma gita was recited in the Sruti style, the standardised style used in sloka and mantra recitations. However, the year 2014 saw the beginning of a new era where a style called Irama Prabu Darmayasa began to be used instead of the standard Sruti style. Soon afterwards, another new style emerged where the dharma gita started to be sung in the Kinanthi Salisirstyle accompanied with Gendhing Ketawang Subakastawa. This research employs theories on cultural changes to analyse the data, such as those by Koentjaraningrat, Gillin & Gillin, and Soemardjan. It discusses factors that trigger the development of a tradition, namely 1) the achievement-motivated development and 2) the social frustration-based development.Such theories are considered suitable to study the field phenomena, particularly the change in dharma gita recitational style that are based on the abovementioned factors. In fact, the writer finds that the on cultural changes are best used to analyse the topic when combined with Supanggah’s theory of style.